2001
DOI: 10.1086/318817
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Apoptosis and Interferon‐γ Production at Sites of ActiveMycobacterium tuberculosisInfection in Human Tuberculosis

Abstract: Pleural tuberculosis (TB) was employed as a model to study T cell apoptosis at sites of active Mycobacterium tuberculosis (MTB) infection in human immunodeficiency virus (HIV)-coinfected (HIV/TB) patients and patients infected with TB alone. Apoptosis in blood and in pleural fluid mononuclear cells and cytokine immunoreactivities in plasma and in pleural fluid were evaluated. T cells were expanded at the site of MTB infection, irrespective of HIV status. Apoptosis of CD4 and non-CD4 T cells in the pleural spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 38 publications
6
77
2
Order By: Relevance
“…Successful chemotherapy resulted in 50% reduction in apoptosis, coinciding with 3-to 8-fold increases in levels of mycobacteria-stimulated IL-2 and IFN-␥, respectively. In another study based on examination of pleural fluid from patients with pleural tuberculosis, the loss of IFN-␥-producing cells is limited specifically to M. tuberculosis-responsive cells (35). These studies provide evidence that T cell apoptosis is biologically significant in the disease process.…”
Section: Discussionmentioning
confidence: 88%
“…Successful chemotherapy resulted in 50% reduction in apoptosis, coinciding with 3-to 8-fold increases in levels of mycobacteria-stimulated IL-2 and IFN-␥, respectively. In another study based on examination of pleural fluid from patients with pleural tuberculosis, the loss of IFN-␥-producing cells is limited specifically to M. tuberculosis-responsive cells (35). These studies provide evidence that T cell apoptosis is biologically significant in the disease process.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, IFN-γ was shown to induce apoptosis of monocytic cells in vitro (55,56), and high levels of this cytokine were also associated with a high level of apoptosis and tissue immunopathology in vivo during intracellular infection (57). Caseous necrosis in human tuberculosis was also recently found to be associated with enhanced IFN-γ and apoptosis (58,59). It is important to point out that the nature and regulation of immune responses in human TB could be more complicated than what we have learned from our current model system.…”
Section: Figurementioning
confidence: 98%
“…After centrifugation, bronchial washing cells were resuspended in FACS buffer (PBS 1Â, pH 7.2, 1% BSA), and counted. Cell surface labeling was performed prior to apoptosis detection, incubating 10 …”
Section: In Situ Detection Of Apoptotic Cells By Colorimetric Tunelmentioning
confidence: 99%
“…Most of these cells are eliminated by apoptosis to restore the T cell compartment to homeostasis [1]. Several experimental observations have suggested that apoptosis of mycobacteriaresponsive T cells, particularly Th1 lymphocytes, decreases production of interferon-gamma (IFN-c), and so reduces the protective immune response in progressive tuberculosis [9][10][11]. Indeed, Th1 cells, which are essential for the control of the infection, are more susceptible than Th0 or Th2 cells to Fasmediated apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%